UPAYA PENINGKATAN MOTIVASI DAN KREATIVITAS SISWA KELAS II SDN 11 SITIUNG DENGAN MENERAPKAN MODEL MIND MAPPING - Subhan, Muhammad (Dharmas Education Journal (DE_Journal), 2023)
The background of the problems that arise in this study is that in class learning, student motivation and creativity still do not appear well during learning activities. As an effort to overcome these problems, the Mind Mapping model was chosen to be applied in classroom learning. The purpose of the research that has been done is to improve the learning process in class and develop students' creativity and motivation in learning activities in class II SD Negeri 11 Sitiung. The target of the research that was carried out was class II students at SDN 11 Sitiung with a total of 18 students. The research method applied is classroom action research (CAR). The research was conducted for 1 cycle. The research was carried out face-to-face with students in class. The method used is planning research, conducting research, observing and reflecting on research results. Through student activity observation sheets and mind mapping assessments, the results of student creativity and motivation were obtained in good criteria. There is an increase in students' creativity and motivation in learning. The results of research by applying the Mind Mapping learning model have an impact on increasing the level of motivation and creativity of students in learning. There were 15 students (83.33%) already motivated in learning activities. Then there were 12 creative students (66.67%) It was proven that the motivation and creativity of students in Class II of SDN 11 Sitiung showed a good impact and Mind Mapping could develop students' motivation and creativity in following and understanding subject matter.